Assessment on soil physico-chemical properties of secondary and rehabilitated forests in Universiti Putra Malaysia Bintulu Sarawak - Fadzil, Muhammad Khairulddin (2018)
Assessment of the associated forest rehabilitation programme regarding soil fertility status by using soil indices could provide fundamental information on soil suitability for species preferences and to improve the technique for future tropical rainforest rehabilitation programmes. This study was conducted to determine the soil physico-chemical properties and to identify the soil fertility status of rehabilitated and secondary forests. Soil samples were collected from both locations which were rehabilitated forest and secondary forest (Nirwana forest) at Universiti Putra Malaysia, Bintulu Campus, Sarawak. The plot size for each site was 20 × 20 m for 18 experimental sites (at different ages after planting) were established, followed by soil sampling at 0-15 cm and 15-30 cm depths randomly. The samples were air-dried and sieved to pass a 2mm mesh sieve for further analysis. Standard soil analysis for physical and chemical properties was used to analyze the soil samples such as soil acidity, soil organic matter, total organic carbon, available P, exchangeable Al, exchangeable cations (Ca, Mg, K, Na) and Cation Exchange Capacity (CEC). The soil fertility status was evaluated using two indices, namely Soil Fertility Index (SFI) and Soil Evaluation Factor (SEF) for both rehabilitated and secondary forests. The results showed that there were significant differences (p<0.05) in pH (water and KCl), CEC, exchangeable Al, Ca, K, Na, total organic carbon and organic matter between depths. The results also showed that the selected physico-chemical properties had significant differences based on the age of planting of rehabilitated forests. The SFI and SEF for rehabilitation forests showed higher value as compared to secondary forests, suggesting forest rehabilitation had improved the fertility status of degraded forestland. In conclusion, both rehabilitated and secondary forests had significant differences based on the selected physical and chemical properties. Moreover, the soil fertility status at the rehabilitated plots was higher than those of the secondary forest, which proved that the forest rehabilitation technique was the ideal planting technique for rehabilitating and replenishing soil fertility status of abandoned degraded shifting cultivation land.